STUDI KASUS PENCANTUMAN LABEL TIDAK HALAL PADA OBAT DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL - Yeti Eka Yuniati; Trini Handayani (Universitas Suryakancana, 2019)
Indonesia is a country with the largest Muslim population in the world, which is about 87% of Indonesia's population is Muslim. The Indonesian state must guarantee its population to consume food, drinks including halal medicine as a command from Allah SWT. Law No. 33 of 2014 concerning Guaranteed Halal Products has not been fully implemented by the Government due to the limitations of Human Resources and facilities in carrying out certification of halal products carried out by the Halal Product Guarantee Agency.The author wants to review the inclusion of non-halal labels on medicines circulating in Cianjur Regency as one of the mandates in the Law. The method used in this study is sociological jurists. The author conducted observations and interviews at pharmacies in Cianjur Regency as well as Pharmacy Installations in the Health Office that distributed medicines to the Central Health Care. In addition, the author also conducted an interview with the drug manufacturer in Sukabumi by conducting an interview with one of the managers of medicines manufacturers as business actors.The results of the study, it turns out that all medicines observed in Cianjur Regency did not include non-halal labels.Â Keywords: Medicines; Muslim; Not Halal Label.